Pengaruh Program Magang Dan Studi Independen Bersertifikat (MSIB) Terhadap Peningkatan Self-Confidence Dan Peluang Kerja Mahasiswa Universitas Hamzanwadi - Riswanto, Agus; Juaini, Muhamad; Aini, Qurratul; Ramdani, Dheta Alvina (Universitas Hamzanwadi, 2024)
This study aims to determine the impact of the certified internship and independent study (MSIB) program on the Self-confidence and job opportunities of Hamzanwadi University students. The design in this study is descriptive quantitative with a survey technique to obtain primary and secondary data and data from the MSIB Higher Education Program Coordinator at Hamzanwadi University. The population in this study was 61 respondents consisting of students who took the MSIB program at Hamzanwadi University from batches 1 - 5 in 2021/2022 - 2023/2024. The sampling technique used was a total sampling technique or census sampling. The data was processed using SPSS statistics ver. 22 with several tests, namely hypothesis analysis, classical assumption tests, and multiple linear regression. Based on the process data, between internship variables and student self-confidence with a t table value smaller than the calculated t (2.002 < 2.705) there is a positive influence, without any significant impact between internship variables and student job prospects with a t table value > calculated t (2.002 > -0.586), independent study variables on self-confidence with a lower calculated t value than the t table (1.784 < 2.002), independent study variables on job opportunities with a higher t table value than the calculated t (2.002 > 0.863), simultaneously there is a large effect between internship variables, certified independent studies (MSIB) on self-confidence with a table F value greater than the calculated F value (11.631 > 3, 16) and significantly affects between internship variables, certified independent studies (MSIB) on job opportunities with a calculated F value < F table (1.210 < 3.16). In R square (R2) on variable Y1, the results obtained were 26.2% and Y2 obtained 0.7%, meaning that students' self-confidence and job opportunities can be explained by the internship and certified independent study variables and the remaining 73.8% and 99.3% are unknown due to the influence of variables outside this study